2020
DOI: 10.3390/pharmaceutics12030215
|View full text |Cite
|
Sign up to set email alerts
|

PGE2 Is Crucial for the Generation of FAST Whole- Tumor-Antigens Loaded Dendritic Cells Suitable for Immunotherapy in Glioblastoma

Abstract: Dendritic cells (DC) are the most potent antigen-presenting cells, strongly inducers of T cell-mediated immune responses and, as such, broadly used as vaccine adjuvant in experimental clinical settings. DC are widely generated from human monocytes following in vitro protocols which require 5–7 days of differentiation with GM-CSF and IL-4 followed by 2–3 days of activation/maturation. In attempts to shorten the vaccine’s production, Fast-DC protocols have been developed. Here we reported a Fast-DC method in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In a good manufacturing practice (GMP)-compliant context, this promotes increased costs in terms of consumables, as well as operator activity in a clean room. Some groups have demonstrated that it is possible to obtain DCs with the safety and efficacy requested by regulatory agencies using short culture protocols in three to five days [35,36].…”
Section: Extensive-vs Short-culture Periodmentioning
confidence: 99%
“…In a good manufacturing practice (GMP)-compliant context, this promotes increased costs in terms of consumables, as well as operator activity in a clean room. Some groups have demonstrated that it is possible to obtain DCs with the safety and efficacy requested by regulatory agencies using short culture protocols in three to five days [35,36].…”
Section: Extensive-vs Short-culture Periodmentioning
confidence: 99%
“…The distinguishing abilities of DCs in capturing and processing tumor antigens and in presenting the processed antigenic fragments to the T cells in tumor-draining lymph nodes result in the generation of tumor-specific Cytotoxic T Lymphocytes (CTLs) that kill tumor cells. [2][3][4][5][6] DCs are capable not only of presenting extracellular antigen fragments in complexation with the major histocompatibility complex (MHC) class II molecules to CD4+ T helper (TH) cells but also of cross-presenting the antigen fragments on MHC class I molecules to CD8+ T cells. 7 Such cross-presentation capability of DCs is crucial in mounting anti-tumor immune responses.…”
Section: Introductionmentioning
confidence: 99%